Analisis Wilayah Kerawanan Bencana Tanah Longsor Menggunakan Citra Lansat 8 Oli dan Citra Sentinel 2-A di Kecamatan Balik Bukit, Kabupaten Lampung Barat - Manullang, Gregoius Tua Chandra; Ridwan, Ridwan; Amien, Elhamida Rezkia; Asmara, Sandi (abe.fp.unila.ac.id, 2024)
This study aims to generate a landslide susceptibility map for Balik Bukit District using geospatial data and analyze the vegetation density from Sentinel 2-A and Landsat 8 OLI imagery to support the identification of landslide-prone areas. The study used SHP data for various parameters including Rainfall, Slope, Geology, Land Cover, Soil Type, and NDVI (Normalized Difference Vegetation Index). The final results consist of thematic maps and a landslide susceptibility map, illustrating the area's risk levels. GIS played a crucial role in mapping, calculations, and analysis. Five landslide susceptibility classes were derived from both Sentinel and Landsat imagery. Sentinel 2-A indicated 1991 Ha as not prone, 6905 Ha as low, 6174 Ha as moderate, 2468 Ha as high, and 710 Ha as very high. Landsat 8 OLI classified 1612 Ha as not prone, 6231 Ha as low, 6899 Ha as moderate, 2565 Ha as high, and 941 Ha as very high. Both imagery types identified Desa Kubu Perahu as very high risk but with different areas: Sentinel 2-A at 169 Ha and Landsat 8 OLI at 215 Ha. Vegetation density significantly influences landslide susceptibility, with Sentinel providing more detailed data, indicating 61 Ha as very sparse compared to 39 Ha by Landsat. Rainfall and Slope are the most dominant factors affecting landslide risk, followed by Geology, Soil Type, Land Cover, and Vegetation Density. Keywords: GIS, Landslide, Lansat 8 OLI, Sentinel, NDVI